2021
DOI: 10.3389/fphar.2021.658072
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Analysis for the Performance of Long-Read-Based Structural Variation Detection Pipelines in Tandem Repeat Regions

Abstract: There has been growing recognition of the vital links between structural variations (SVs) and diverse diseases. Research suggests that, with much longer DNA fragments and abundant contextual information, long-read technologies have advantages in SV detection even in complex repetitive regions. So far, several pipelines for calling SVs from long-read sequencing data have been proposed and used in human genome research. However, the performance of these pipelines is still lack of deep exploration and adequate co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 42 publications
(52 reference statements)
1
4
0
Order By: Relevance
“…When comparing SV type across sexes, frequencies were similar and within 5% variability between males and females for length and count. The frequency and length of rSVs in our study closely correspond with population frequencies seen in other studies (Kosugi et al 2019; Guo et al 2021).…”
Section: Resultssupporting
confidence: 91%
“…When comparing SV type across sexes, frequencies were similar and within 5% variability between males and females for length and count. The frequency and length of rSVs in our study closely correspond with population frequencies seen in other studies (Kosugi et al 2019; Guo et al 2021).…”
Section: Resultssupporting
confidence: 91%
“…In summary, different strategies investigate various variant signals (values and/or distributions) in sequencing data and can deal with diverse sequencing data with different signals and their distributions. Furthermore, some empirical studies (Luan al., 2020;Kosugi et al, 2019;Guo et al, 2021) have been conducted to validate this phenomenon. A set of popular callers is compared on some benchmarking datasets in these studies, and the results showed that most callers have an edge for specific data.…”
Section: Introductionmentioning
confidence: 95%
“…According to this study's testing, some features, such as read length and sequencing depth, are useful, while others are not. Furthermore, some review studies have proposed some sequencing data features, such as the size of SVs and the proportion of SVs in tandem repeat regions, which have been shown to differentiate the performance of SV callers (Kosugi et al, 2019;Zook et al, 2020;Guo et al, 2021).…”
Section: Meta-feature Extractionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent studies highlighted the need for LRS-specific algorithms for analysis of LRS data ( DeJesus-Hernandez et al 2021 ; Guo et al 2021 ; Miller et al 2021 ). While various combinations of base-caller algorithms and tandem-genotypes could provide estimates for the ABCA7 VNTR length, expanded alleles reaching more than 10 kb were better captured by a newly developed algorithm, NanoSatellite, which directly assesses electronic current data such as that obtained by nanopore sequencing ( De Roeck et al 2019 ).…”
Section: Part 1: Technological Advances and Repeat Disease Mutation D...mentioning
confidence: 99%